2001
DOI: 10.1161/01.hyp.38.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Potentiation by Angiotensin-(1-7) and ACE Inhibitors Correlates With ACE C- and N-Domain Blockade

Abstract: Abstract-ACE inhibitors block B 2 receptor desensitization, thereby potentiating bradykinin beyond blocking its hydrolysis. Angiotensin (Ang)-(1-7) also acts as an ACE inhibitor and, in addition, may stimulate bradykinin release via angiotensin II type 2 receptors. In this study we compared the bradykinin-potentiating effects of Ang-(1-7), quinaprilat, and captopril. Porcine coronary arteries, obtained from 32 pigs, were mounted in organ baths, preconstricted with prostaglandin F 2␣ , and exposed to quinaprila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 31 publications
(24 reference statements)
6
89
1
1
Order By: Relevance
“…Angiotensin-(1-7) is known to inhibit the ACE C-domain, resulting in acting as an ACE inhibitor. 22 Although the mechanism of olmesartan to inhibit ACE activity remains unclear, olmesartan's effect of lifespan extension may involve the attenuation of vascular ACE activity, in addition to the direct AT 1 receptor blockade in this study. Significance of high affinity ARBs S Takai et al…”
Section: Discussionmentioning
confidence: 76%
“…Angiotensin-(1-7) is known to inhibit the ACE C-domain, resulting in acting as an ACE inhibitor. 22 Although the mechanism of olmesartan to inhibit ACE activity remains unclear, olmesartan's effect of lifespan extension may involve the attenuation of vascular ACE activity, in addition to the direct AT 1 receptor blockade in this study. Significance of high affinity ARBs S Takai et al…”
Section: Discussionmentioning
confidence: 76%
“…Unlike other vascular beds, where A 779, a putative Ang 1-7 antagonist (Santos et al, 1994), inhibits the vasodilator effect of Ang 1-7 (Bayorh et al, 2002;Ren et al, 2002), our results demonstrate that the vasodilator effect of Ang 1-7 on the MVB could involve other receptors, given that A 779 does not inhibit Ang 1-7 vasodilation. BK appears to modulate Ang 1-7-induced vasodilation, since several reports have shown that the vasodilator effect of BK is enhanced by Ang 1-7 and vice versa (Brosnihan et al, 1996;Gorelik et al, 1998;Almeida et al, 2000;Fernandes et al, 2001;Tom et al, 2001). Also, the involvement of BK in the vasodilator effect of Ang 1-7 is suggested by Brosnihan et al (1996), who demonstrated that the vasodilator effect of Ang 1-7 was inhibited by HOE 140.…”
Section: Rs De Moura Et Al Angiotensin Ii-dependent Vasodilation 863mentioning
confidence: 96%
“…191 Moreover, a C-selective inhibitor will have a lower propensity for excessive B 2 receptor stimulation by BK, which is maximal when both the N-and Cdomains are inhibited. 192 Therefore, a highly selective C-domain inhibitor has the potential for effective BP control with reduced vasodilator-related side effects.…”
Section: Future Of Aceismentioning
confidence: 99%